Do bad habits bring a double constipation risk? - Santacruz, Carlos Cerdán; López, Mario Ortega; García, Marta Vigara; Pérez, Cristina Fernández; Miguel, Javier Cerdán (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Good dietary habits, fluid intake, and regular exercise are considered to ease defecation although very few cases of chronic constipation can be managed through these approaches alone. Good defecation habits are recommended to avoid chronic constipation; however, the literature regarding this remains scarce. In this paper, we aimed to assess the association of bad habits concerning defecation, such as postponing, reluctance, or avoiding defecation anywhere but at home, with chronic constipation. Materials and Methods: This was a cross-sectional observational study including subjects from a tertiary hospital taskforce. In total, 415 of 910 eligible subjects were randomly selected. A cluster of questionnaires easy to understand and fill out was distributed. The questionnaires included queries regarding demographic data; past medical history; the presence of constipation; and dietary, other lifestyle, and defecation habits. The Rome III criteria for chronic constipation were also recorded. Results: In total, 24.3% of the subjects considered themselves constipated, and 26.5% fulfilled the Rome III criteria for constipation. There were obvious differences in constipation prevalence by sex (men 5% vs. women 31%). Fiber-rich diet, fluid intake, and exercise habits were not related to constipation. Defecation habits significantly correlated with the presence or absence of constipation: regular schedule (OR 0.39; CI 95% 0.23-0.67), persistently postponing defecation (OR 1.94; CI 95% 1.13-3.34), or avoiding defecation anywhere but at home (OR 2.38; CI 95% 1.4-4.1). Conclusion: Compared with dietary habits, behavioral aspects surrounding defecation are more related to chronic constipation. Our results indicate that the modification of these bad habits may be the first step in chronic constipation treatment. Cite this article as: Cerdán-Santacruz C, Ortega-López M, Vigara-García M, Fernández-Pérez C, Cerdán-Miguel J. Do bad habits bring a double constipation risk? Turk J Gastroenterol 2018; 29: 580-7.